2022
DOI: 10.18103/mra.v10i10.3318
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and Bile Acid Metabolomic Analysis of Fecal Microbiota Transplantation for Recurrent Clostridiodes Difficile and/or Inflammatory Bowel Diseases

Abstract: Background. Fecal microbiota transplantation (FMT) is an effective treatment of recurrent Clostridioides difficile infections (rCDI), but has more limited efficacy in treating either ulcerative colitis (UC) or Crohn’s disease (CD), two major forms of inflammatory bowel diseases (IBD). We hypothesize that FMT recipients with rCDI and/or IBD have baseline fecal bile acid (BA) compositions that differ significantly from that of their healthy donors and that FMT will normalize the BA compositions. Aim. To study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Our results confirmed previous trends that primary bile acids (i.e., glycocholic acid and taurocholic acid) decreased, and secondary bile acids (i.e., taurodeoxycholic acid, lithocholic acid, deoxycholic acid) increased following FMT (Figure 4A), reflecting recolonization of the gut with active microbiota. 29,54,61,62 N-acetylated amino acids (Figure 4B) have been reported to decrease with C. dif f colonization; 63 Nacetylarginine, N-acetyllysine, N-acetylvaline, N-acetylthreonine, and N-acetylglutamic acid were found to increase significantly following FMT. Prolylhydroxyproline, an amino acid that is beneficial for C. dif f growth, and released during toxin-mediated CDI from host collagen, 62−65 was also found to decrease substantially following FMT.…”
Section: Merging Identifications and Significantly Differential Featu...mentioning
confidence: 91%
“…Our results confirmed previous trends that primary bile acids (i.e., glycocholic acid and taurocholic acid) decreased, and secondary bile acids (i.e., taurodeoxycholic acid, lithocholic acid, deoxycholic acid) increased following FMT (Figure 4A), reflecting recolonization of the gut with active microbiota. 29,54,61,62 N-acetylated amino acids (Figure 4B) have been reported to decrease with C. dif f colonization; 63 Nacetylarginine, N-acetyllysine, N-acetylvaline, N-acetylthreonine, and N-acetylglutamic acid were found to increase significantly following FMT. Prolylhydroxyproline, an amino acid that is beneficial for C. dif f growth, and released during toxin-mediated CDI from host collagen, 62−65 was also found to decrease substantially following FMT.…”
Section: Merging Identifications and Significantly Differential Featu...mentioning
confidence: 91%
“…It involves transplantation of feces from a healthy donor to a receiver with dysbiosis (Gupta et al., 2016 ; Shasthry, 2020 ). This procedure is used to treat conditions such as inflammatory bowel diseases (Kedia et al., 2022 ; Tan et al., 2020 ), and has shown to correct dysbiosis, increase SCFA production (Su et al., 2022 ; Zhang, Jian, et al., 2023 ), restore normal BA composition, and alleviate liver injury in mice and humans (Bustamante et al., 2022 ; Hu et al., 2022 ; Liu, Fan, et al., 2021 ; Ramos et al., 2022 ; Weingarden et al., 2014 ; Xue et al., 2022 ).…”
Section: Targeting the Gut–liver Axismentioning
confidence: 99%
“…To date, multiple studies have reported structural changes to the microbiota in rCDI after FMT 14,[22][23][24][25][26] . Specifically, they have observed an increase in the number of commensal bacteria 4 from the Phyla of Firmicutes and Bacteroidetes, and a decrease in Proteobacteria 27 .…”
mentioning
confidence: 99%
“…Specifically, they have observed an increase in the number of commensal bacteria 4 from the Phyla of Firmicutes and Bacteroidetes, and a decrease in Proteobacteria 27 . These changes are always accompanied with an increase in alpha diversity 14,[22][23][24][25][26] . While it is not known why an increase in alpha diversity allows for a successful FMT, a recent study found an increase in diversity were able to exclude both Klebsiella pneumoniae and Salmonella enterica serovar Typhimurium from colonizing the gut through the mechanism of nutrient blocking, by consuming nutrients the pathogen needed 28 .…”
mentioning
confidence: 99%
See 1 more Smart Citation